Strong plasmonic enhancement of single molecule photostability in silver dimer optical antennas - Kaminska Izabela (Nanophotonics, 2018)
Photobleaching is an effect terminating the photon output of fluorophores, limiting the duration of fluorescence-based experiments. Plasmonic nanoparticles (NPs) can increase the overall fluorophore photostability through an enhancement of the radiative rate. In this work, we use the DNA origami technique to arrange a single fluorophore in the 12-nm gap of a silver NP dimer and study the number of emitted photons at the single molecule level. Our findings yielded a 30× enhancement in the average number of photons emitted before photobleaching. Numerical simulations are employed to rationalize our results. They reveal the effect of silver oxidation on decreasing the radiative rate enhancement.